Cumulative training dose`s effects on interrelationships between common training-load models during basketball activity - Scanlan,A. T.; Fox, J. L.; Borges, N. R.; Dascombe, B. J.; Dalbo, V. J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: The influence of various factors on training-load (TL) responses in basketball has received limited attention. This study aimed to examine the temporal changes and influence of cumulative training dose on TL responses and interrelationships during basketball activity.